Using: Study of Multiculturalism and Identity Politics on Local Islam - Abdul Halim (Universitas Islam Negeri (UIN) Salatiga, 2019)
This research reviews multiculturalism and identity politics with the object of Using Islam. Using ethnic is a native of Banyuwangi which is predominantly Muslim. The existence of the Using community in addition to describing the spirit of multiculturalism also reflects the spirit of identity politics. Using people live in Java and speak Old Javanese, but they tend to identify themselves as Using ethnicity rather than Javanese. They also refer to the language as Using language, not Javanese. Becoming its own ethnicity makes the Using community have a number of distinctive cultural traditions and systems, including Islamic practices. Islamic values are acculturated with Using's local values and form a unique religious culture system. Socio-anthropologically, the persistence of Using's ethnic attitude is a reflection of identity politics that arises because of past historical experiences that were colonized by other powers, including the Islamic Mataram kingdom.